Characterization of two competing risks models with Weibull risks (2015)
Competing risks are used to model life of systems with multiple failure modes where the observed failure is the minimum of the possible individual failures times. This research studies the effect ofignoring the risks by considering how well a single Weibull model approximates the competing risks model with Weibull risks. As a first approach to the problem this is done for a model with Weibull independent risks and for a specific model with Weibull dependent risks. Ignoring the risks may or not have a strong effect in the competing risks model and it would be of interest to characterize situations where ignoring the risks can cause serious biases in the competing risks model. The objective is to characterize the effect of the risks and their interdependence in the competing risks model, when the risks are Weibull distributed. Some recommendations are given on the correct use of these models.